School Emergency Preparedness Study, United States, 2018 - Silvia, E. Suyapa ([Verlag nicht ermittelbar], 2022)
The School Emergency Preparedness Study, United States, 2018, was conducted to better understand the state of knowledge concerning violent emergency preparedness in schools and the interrelationship between federal, state, district, and school perspectives on safety planning. RTI International conducted a two-year study in four phases. In Phase I, the project team reviewed federal and state guidelines and mandates for school safety planning. In Phases II and III, a survey was administered to district safety and security directors and superintendents, then the team reviewed guidelines and mandates for a subset of districts. In Phase IV, interviews were conducted with administrators from 37 schools and results were analyzed from all four phases.